Sumur dan Budaya Suku Kajang; Kearifan Lokal Suku Kajang - Rusdiansyah Rusdiansyah (Jurnal Commercium: Kajian Masyarakat Kontemporer, 2019)
This study aims to determine the other functions of wells in the Kajang tribal community. The Kajang tribe is a tribe that is still very thick in the culture of its people, like the use of technology such as handphone, TV, etc. not permitted. This makes the process of communication or community interaction limited to direct interaction, in contrast to the general public who have used technology such as handphone etc. This study used descriptive qualitative method. In this study, it was found that the Kajang tribal community depended on their water needs in only one well or water source in each of their hamlets, so this well became one of the gathering places for the Kajang tribal community. The well is a community media for exchanging information, chatting, and even sharing important information to be known by all people of Kajang tribe.